Blau syndrome: A case report with unusual symptoms and literature review (Annals of Medical Research, 2025)
Blau syndrome (BS) is an autosomal dominant disease that is brought on by changes in the gene that codes for the NOD-like receptor (NLR) protein (NOD2). It is characterized by the trinity of granulomatous polyarthritis, rash, and uveitis One-third to one-half of BS patients were found to have atypical symptoms. This case report presents the clinical experience of a BS patient with unusual findings at a tertiary care center in Istanbul.A 7-year-old male patient admitted to the outpatient clinic with a complaint of abdominal pain. There were rash attacks with fever for 2 years. He has had abdominal pain that has been going on for years and was previously operated on due to intussusception. There were no hereditary familial diseases found in the patient's family history. In the superficial tissue ultrasonography, intussusception was observed in an intestinal segment. Pathological examination of segmental resection of ileum, cecum, and appendix showed that there were findings of acute appendicitis, peritonitis with surface fissuration, and ulcer. The skin biopsy showed noncaseating, granulomatous infiltration with epithelioid cells and lymphocytes.  In the genetic test, the NOD2 c.1835C˃T heterozygous mutation was detected. Based on this, BS was diagnosed. The patient was started on adalimumab and additional colchicine treatment.This syndrome can mimic other systemic inflammatory diseases in the early stages. This case report shows that we need to consider the diagnosis of BS in more detail in cases who raise clinical suspicion.
Keywords: Blau syndrome; Invagination; NOD2 mutation